2021
DOI: 10.1002/clc.23566
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of patients undergoing coronary sinus reducer implantation ‐ A multicenter study

Abstract: Background Coronary sinus (CS) narrowing by reducer implantation has emerged as a safe and effective therapy for patients suffering from refractory angina. However, data regarding the clinical benefit of this treatment over time is lacking. Methods Patients undergoing successful reducer implantation were enrolled prospectively to clinical registries at three medical centers. Those with more than 2‐years of follow‐up were included in the present analysis. Peri‐procedural data, data regarding adverse events, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The cost-effectiveness of the reducer was expressed as an ICER, defined as the differential in the cumulative costs relative to the difference in cumulative QALYs of the reducer and SoC. Contrary to the assumptions made by Gallone et al ( 13 ), which anticipated a decline in effectiveness over time, our analysis supports the sustained and consistent efficacy of the device, as previously documented in the efficacy section and corroborated by literature ( 14 17 ). For this reason, a decrease in effectiveness over the time horizon considered is not assumed in the model.…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…The cost-effectiveness of the reducer was expressed as an ICER, defined as the differential in the cumulative costs relative to the difference in cumulative QALYs of the reducer and SoC. Contrary to the assumptions made by Gallone et al ( 13 ), which anticipated a decline in effectiveness over time, our analysis supports the sustained and consistent efficacy of the device, as previously documented in the efficacy section and corroborated by literature ( 14 17 ). For this reason, a decrease in effectiveness over the time horizon considered is not assumed in the model.…”
Section: Methodssupporting
confidence: 86%
“…While this study holds significant relevance for its insights into the cost-effectiveness of introducing new technologies within the Italian national healthcare system, it is not without limitations. In contrast to the findings presented by Gallone et al in 2019 ( 13 ), subsequent research ( 14 17 , 19 , 21 ) has suggested that the efficacy of the reducer may remain stable over an extended period. Additionally, the implantation of the reducer has been shown not to affect blood pressure and heart rate metrics pre and post-procedure, further supporting the notion that its beneficial impacts are directly linked to the device itself rather than alterations in medical treatment.…”
Section: Limitationsmentioning
confidence: 64%
See 3 more Smart Citations